Higher Tax and Less Work: An Optimal Response to Relative Income Concern - Felix FitzRoy; Jim Jin; Michael A. Nolan (Institute of Labor Economics (IZA), 2019)
There is much evidence that relative income concern reduces subjective wellbeing and raises labour supply – 'keeping up with the Joneses' (KUJ), while increasing use of social media and growing inequality encourage comparison. Models with one or two agent –types generally miss the policy relevant dimension of labour force participation, so we include a distribution of wages with intensive and extensive margins of labour supply, both of which are increased by comparison. The optimal tax response increases with comparison, but, surprisingly, dominates the comparison effect and reduces individual labour supply, thus reversing KUJ, and maintains constant employment, independent of comparison.
Keywords: H24; D63; 330; income comparison; maxi-min; inequality; unemployment